The Influence of Wind Shielding and Train-Induced Wind on the Vibration of a Train-Bridge System - Yujing Wang; Xuexiang Xv; Shanshan Wang; Qinghai Guan (Advances in Civil Engineering)
The aerodynamic forces of the system were obtained based on a 3D aerodynamic model, and a dynamic analysis model of the train-bridge coupling system was established to compare the vibration responses of the train and bridge with and without a wind barrier to fully consider the wind shielding effect and train-induced wind effect on the vibration of a train-bridge system. The results show that the combined wind direction and the direction of the operating train are at an angle. Although the shape of the leading and trailing cars is the same, their wind load values are not the same due to the influence of the train wind. Because of the perforations, the vortex between the wind barrier and the train’s windward surface varies in a complicated fashion. The airflow traveling through the holes has a negative value because it circulates at the intersection of the windward surface and the top surface of the car body. The vehicles’ lateral wheel force, derailment factor, offload factor, and overturning factor are all lowered when the wind barrier is erected. The shielding effect of the wind barrier on the head car is more noticeable when it comes to lateral wheel force and derailment factor. With a wind barrier installed, the wind field surrounding the bridge is very complex, resulting in a modest decrease in vertical displacement.